Radiasi Sinar Gamma Pada Pertumbuhan Tanaman Sirsak (Annona muricata Linn) - Siregar, Ghojali; Sitanggang, Kamsia Dorliana; Mustamu, Novilda Elizabeth; Saragih, Siti Hartati Yusida (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2024)
This research aims to determine the growth response (Annona murikata Linn)’by using the method of sinargama radiation with doses of 0 KGY, 0.2 KGY, 0.5 KGY, 0.75 KGY. which was carried out in the Tanjung medan Garden, labuhan batuselatan Regency. The study was conducted from March to May 2022. Ysng method used randomized design group (RAK), which is used to determine the growth response ( Annona murikatLi) using radiation sinargama.The parameters observed were plant height (cm) and number of leaves (strands).Planting height in the last week showed that the dose of 0 KGY, 0.5 KGY, and 0.75 KGY,did not differ significantly from the dose of 0.2 KGY, with a height of 23.20 (cm) This is because it is not too dangerous the influence of these doses for the growth of soursop plants. and the number of leaves in the last week showed that the dose of 0 KGY, 0.5 KGY, and 0.75 KGY,did not differ significantly from the dose of 0.2 KGY,with a number of 6 strands. The low number of leaves produced due to radiation sinargama at high doses can cause changes in plant chromosomes that affect the growth of leaf balak. Keywords: sinargama radiation, Annona murikat Lin